Kisah Dzu al-Qarnain dalam Al-Qur’an: Fungsi dan Urgensi bagi Dakwah Nabi Muhammad - Nor Faridatunnisa (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2022)
The research related to the story of Dzu al-Qarnain in the Koran, still focus on who the “figure” Dzu al-Qarnain is, not to reveal the “urgency” that lies behind the text. In fact, the value of that story that should be revealed to be used in religious practice. The structure of Dzu al-Qarnain’s story which begins with a question also indicates that there is a patte’n of direct Qur'ani da’wah between God, Muhammad, and Arab society. Therefore, the study of the purpose of the of Dzu al-Qarnain’s story in the Qur’an for Muhammad’s da’wah is important. This research is a type of qualitative research that is a library research. The method used in this research is descriptive-analytic. The data about the story of Dzu al-Qarnain will be presented, and than will be analized with a historical approach to find the purpose or urgency of this story for Muhammad’s da’wah. The results of the study show that the urgency of mentioning the story of Dzu al-Qarnain in Muhammad’s era includes two aspects, that general aspect and special aspect. In general, the aim was to provide a “real example” to the Meccan society at that time, which tended to be materialistic. As for specifically aiming to prove Muhammad’s competence that he is truly the messenger of Allah who had the comprehensive knowledge. Thus, it can be stated that the story of Dzu al-Qarnain contains missionary messages that were important for Muhammad as the main figure of da’wah at that time.